2015
DOI: 10.1179/1743132815y.0000000018
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier dysfunction following traumatic brain injury: correlation of Ktrans(DCE-MRI) and SUVR (99mTc-DTPA SPECT) but not serum S100B

Abstract: The correlation of SPECT with DCE-MRI suggests that either scan may be used to assess post-traumatic BBB damage. We could not support serum S100B to be an accurate measure of BBB damage when sampled a number of days following injury but the small number of patients, the heterogeneity in TBI patients and the delay following injury makes any firm conclusions regarding S100B and BBB difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Further, even though Q A is the current golden-standard method for BBB integrity, the TBI field would benefit from a new BBB integrity biomarker. Radiological tools, notably dynamic enhanced contrast magnetic resonance imaging, have been utilized in other neurological disorders to assess BBB disruption [9], but has as of yet been but sparsely utilized in the TBI setting [76,77]. Meanwhile, we show that BBB disruption measured utilizing Q A is a novel important outcome predictor following severe TBI.…”
Section: Tbi Studies Benefit From Csf But Warrant a New Bbb Disruptimentioning
confidence: 81%
“…Further, even though Q A is the current golden-standard method for BBB integrity, the TBI field would benefit from a new BBB integrity biomarker. Radiological tools, notably dynamic enhanced contrast magnetic resonance imaging, have been utilized in other neurological disorders to assess BBB disruption [9], but has as of yet been but sparsely utilized in the TBI setting [76,77]. Meanwhile, we show that BBB disruption measured utilizing Q A is a novel important outcome predictor following severe TBI.…”
Section: Tbi Studies Benefit From Csf But Warrant a New Bbb Disruptimentioning
confidence: 81%
“…To our knowledge, this study is one of the few clinical studies applying DCE MR imaging on mTBI patients. Unlike previous studies (20,31), we applied automatic segmentation and A. Mean K trans value in bilateral cerebral cortex was significantly higher in mTBI patients (median, 0.0104 x 10 -1 min -1 ) than in controls (median, 0.0084 x 10 -1 min -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…We assessed how a trauma-induced BBBD affects brain biomarker concentrations in blood. Even though some radiological techniques have been proposed to quantify BBBD, 58,59 Q A remains the gold standard assessment, [19][20][21][22][23][24][25] because the 67 kDa protein albumin lacks intracranial synthesis, 19 is not catabolized in the CNS, 60 and has a 200 times lower concentration in CSF compared with serum. 19 We found that whereas Q A on a group basis had a decreasing trend over the 1st week, patients who had normal Q A values at study onset maintained normal values throughout the study period and vice versa.…”
Section: The Disrupted Bbb In Tbimentioning
confidence: 99%